Analysis of 12 GWAS-Linked Loci With Parkinson’s Disease in the Chinese Han Population - Fan, Liyuan; Shi, Changhe; Hu, Xinchao; Zhang, Zhongxian; Zheng, Huimin; Luo, Haiyang; Fan, Yu; Zhang, Shuo; Hu, Zhengwei; Yang, Jing; Mao, Chengyuan; Xu, Yuming (Frontiers in Neurology, 2021)
A recent large-scale European-originated genome-wide association study identified 38 novel independent risk signals in 37 loci for Parkinson's disease (PD). However, whether these new loci are associated with PD in Asian populations remains elusive. The present study aimed to explore the relationship between the 12 most relevant loci with larger absolute values for these new risk loci and PD in the Chinese Han population. We performed a case-control study including 527 PD patients and 435 healthy controls. In the allele model, it was found that rs10748818/GBF1 was associated with PD in the Chinese Han population [p = 0.035, odds ratio (OR) 1.221, 95% confidence interval (CI) 1.014–1.472